APLIKASI METODE DISKUSI DAN TUGAS DALAM MENINGKATKAN HASIL BELAJAR SISWA SMPN 2 PEKALONGAN TAHUN PELAJARAN 2011/2012 - Endri Sugianto (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
The aim of the research was to increasing of science learning echievement. The research was to implemented by the Classroom Action Research (CAR) in SMPN 2 Pekalongan class VIII1 academic year 2011/2012. The result of this research was the application of the discussion and assignment method, students learning achievement increase from the cycle I to cycle II by 16,12%. Based on the research the researcher suggest that the scence teachers need to apply the discussion and assignment method to increase achievement of science. Kata kunci : Metode Diskusi dan Tugas, Hasil Belajar Siswa